Financial Institutions, valuations, merger, and acquisitions : the fair value approach - Rezaee, Zabihollah (New York Chicester John Wiley & Sons Inc., 2001)
This book provides maximum flexibility in choosing the amount and order of materials on valuations, merger, and acquisitions for financial institutions.
Includes bibliographical references and index
osa 22/8/2016
Loans
Keywords: Bank mergers; Banks and banking; Sale of banks; Financial institutions - Mergers; Financial instituions - Valuation; Financial institutions - Purchasing; Consolidation and merger of corporations - Law and legislation; United States